2021
DOI: 10.1177/01436244211054443
|View full text |Cite
|
Sign up to set email alerts
|

Associations between indoor soundscapes, building services and window opening behaviour during the COVID-19 lockdown

Abstract: Results of an online survey conducted during the COVID-19 lockdown among 848 home workers living in London (United Kingdom) and in Italy are reported with a focus on (1) the impacts of building services on the perception of the acoustic environment while working and relaxing at home and (2) the factors associated with window opening behaviour. The analyses showed no significant difference in soundscape appropriateness for relaxation depending on the heating, ventilation and cooling system typologies, and in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Observing the use of curtains among the participants, it was found that most of the isolators chose to keep the curtains opened except during sleep and on rainy days. It supports the results of the study [66][67][68] that people in isolation need more daylight and a view from the window. In addition, students may be in a better psychological state when exposed to more artwork and greenery [69,70].…”
Section: Environment Adjusting Behavior and Purposesupporting
confidence: 86%
“…Observing the use of curtains among the participants, it was found that most of the isolators chose to keep the curtains opened except during sleep and on rainy days. It supports the results of the study [66][67][68] that people in isolation need more daylight and a view from the window. In addition, students may be in a better psychological state when exposed to more artwork and greenery [69,70].…”
Section: Environment Adjusting Behavior and Purposesupporting
confidence: 86%
“…A perceived importance of dominance of building services in the indoor soundscape, as compared with natural ventilation, which was found to be preferable in a second study by the same team (Torresin et al 2022). The use of natural ventilation was seen as preferable for reducing GHG emissions (compared to air conditioning), however levels of outdoor noise or air pollution could limit uptake of this option (Torresin et al 2021a).…”
Section: Air Pollution and The Interface Between Outdoor And Indoor E...mentioning
confidence: 98%
“…The indoor environment became increasingly important during the lockdown, and studies considering the home working space were numerous, but out of scope for this study. One set of work addressed a combination of ventilation, window opening behaviour and indoor soundscapes for dwellings in the UK and Italy (Torresin et al 2021a). The primary difference between dwellings was the availability of air cooling systems in Italy, compared to window opening in the UK.…”
Section: Air Pollution and The Interface Between Outdoor And Indoor E...mentioning
confidence: 99%
“…Additionally, in London, Torresin and colleagues conducted an online survey to characterize the indoor soundscape during confinement [102][103][104][105]. The survey targeted London residents who worked from home during confinement, focusing on two activities performed at home during the pandemic: working and relaxing.…”
Section: Buildings and Homesmentioning
confidence: 99%